2018
DOI: 10.1002/vjch.201800079
|View full text |Cite
|
Sign up to set email alerts
|

High‐purity amorphous silica from rice husk: Preparation and characterization

Abstract: Amorphous silica has a wide range of applications in chemical, biological and environmental sectors. In this work, we studied the preparation of amorphous silica from rice husk, an abundant silica-rich agricultural waste in Vietnam. We investigated and compared two methods of preparation: (1) via selective removal of alkaline and alkaline-earth oxides from rice husk ash to yield amorphous silica; and (2) via selective precipitation of silica from aqueous solutions which had been prepared by dissolving rice hus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…For the extraction of MSNs, the fairly white RHA produced from calcination at 650 °C was used as the precursor material. In a previous study, RHA colouration has been associated with Si purity; lighter colour RHA correlates to higher purity whereas a darker RHA confers lower purity 56 . Previous studies reported that amorphous RHAs are produced at 550-800 °C while at higher temperatures (> 800 °C), the RHA takes up the crystalline form 18,57,58 .…”
Section: Discussionmentioning
confidence: 86%
“…For the extraction of MSNs, the fairly white RHA produced from calcination at 650 °C was used as the precursor material. In a previous study, RHA colouration has been associated with Si purity; lighter colour RHA correlates to higher purity whereas a darker RHA confers lower purity 56 . Previous studies reported that amorphous RHAs are produced at 550-800 °C while at higher temperatures (> 800 °C), the RHA takes up the crystalline form 18,57,58 .…”
Section: Discussionmentioning
confidence: 86%
“…However, other researchers reported relatively lower yield; 18–20% SNPs from rice husk ( Setyawan et al., 2019 ). This variation is expected and might be due to the environmental conditions where the plants grow like other natural products ( Ngoc et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The OPDCA at 600C was chosen to be treated with 140 mL of 5M NaOH solution. Subsequently, a broad diffraction peak at 2θ=22° confirmed that the crystalline silica has transformed into an amorphous form after being treated with an alkaline solvent, which is represented by the bellshaped peak observed in the spectrum (Bakar et al, 2016;Mosisa et al, 2019;Ngoc et al, 2018). No sharp peak was observed on the diffraction pattern, which strongly proved that the crystalline silica has not been exhibited (Anuar et al, 2018).…”
Section: Structural Phase Analysismentioning
confidence: 85%